Beneficial effects of peer support in psychiatric hospitals. A critical reflection on the results of a qualitative interview and focus group study. (3rd May 2020) - Otte, Ina; Werning, Anna; Nossek, Alexa; Vollmann, Jochen; Juckel, Georg; Gather, Jakov
Abstract: Background: The implementation of peer support work in psychiatric hospitals is a relatively recent development. Consequently, the effects of peer support work on mental health professionals, patients and peer support workers (PSWs) are mostly unknown. Aims: To explore the beneficial effects of peer support work in detail and to reflect critically on potential sources of misunderstanding. Method: (1) Nine open-ended, semi-structured interviews with PSWs and (2) five focus groups with mental health professionals plus one focus group with PSWs. The data were analyzed using qualitative content analysis. Results: Our data show various beneficial effects on patients, such as the themes "less professional distance, " "more time for one-on-one attendance" and "a role model for recovery." Themes that emerged for mental health professionals were, amongst others, "adding a new perspective, " "improved continuity in treatment offers" and "preserving a respectful tone in meetings." Conclusions: It is necessary to minimize the risk of role confusion to achieve the beneficial potential of peer support work. A thorough education on what peer support work can and cannot deliver is essential and could help to foster its successful implementation.